Investigating unmetabolized polycyclic aromatic hydrocarbons in adolescents' urine as biomarkers of environmental exposure. (July 2016) - De Craemer, Sam; Croes, Kim; van Larebeke, Nicolas; Sioen, Isabelle; Schoeters, Greet; Loots, Ilse; Nawrot, Tim; Nelen, Vera; Campo, Laura; Fustinoni, Silvia; Baeyens, Willy
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are of interest to human biomonitoring studies due to their carcinogenic potential. Traditionally metabolites of these compounds, like 1-hydroxypyrene, are monitored in urine, but recent methods allow the determination of the parent compounds in urine, which give additional information regarding sources and toxicity of PAHs. In order to assess the feasibility of incorporating these methods in a human biomonitoring study, the 16 USEPA parent PAHs were determined in 20 urine samples. These samples were obtained from 10 boys and 10 girls aged 14–16 years, participating in the third Flemish Environment and Health Study (Flanders, Belgium). Of these 16 parent PAHs, nine could be determined in more than 95% of the samples and three (including benzo( a )pyrene) in more than 50%. Several correlations were found between different PAHs, but not between pyrene and its metabolite 1-hydroxypyrene. Diagnostic PAH ratios in urine and air samples pointed towards combustion sources and are in line with the ratios in environmental samples. Benzo( a )pyrene, naphthalene and fluorene have the highest carcinogenic potential in our cohort, when using toxic equivalency factors. Some associations between PAH congeners and determinants of exposure were found, while fluorene and acenaphthylene were positively associated with thyroid hormone levels and benzo( a )pyrene showed a positive correlation with DNA damage by comet assay. These results confirm that parent PAHs in urine are useful as biomarkers of exposure in biomonitoring studies. Highlights: 12 of 16 parent PAHs were quantified in urine of Flemish adolescents. Benzo( a )pyrene showed a positive association with DNA damage. Parent PAH congeners do not correlate with 1-hydroxypyrene. Parent PAHs are useful as exposure biomarkers for biomonitoring studies.